Telepathic Proficiency - A Factual Threat on Humanity - Gurevitz, Michael; Dagan, Roee (European Journal of Applied Sciences, 2024)
The molecular mechanism underlying human cognition is still a ‘black box’ despite intense brain research. The 1.4 kg brain tissue contains billions of nerve cells (neurons) connected via synaptic junctions that transport electrical and chemical signals toward target regions, while its functioning is associated with activation or inactivation of variable neuronal networks, demonstrating high plasticity. In recent years, imaging techniques enabling visualizatuin of neurons and synapses have been developed, monitoring brain centers that ‘light up’ by external stimuli (e.g., ref 1). Moreover, various non-invasive techniques for real time monitoring of spatio-temporal (position and time) brain activity upon external stimuli (e.g., sensory, cognitive, motor, regulatory) have been developed e.g., electroencephalography (EEG), position emission tomography (PET), near infrared spectroscopy (NIRS), magnetoencephalography (MEG), and functional magnetic resonance imaging (fMRI) (e.g., ref. 2), but despite this impressive repertoire, the processing mechanisms by which activation of certain neuronal networks constitute our consciousness, soul, or abstractive competence (thinking, spiritual perception, inventive productivity, build-up of moral principles, emotions, memories) remain unclear. These open questions are especially puzzling in light of the central role of the brain in controlling our physical and mental abilities and successful mapping of activated structural regions involved in various functions, as well as in light of the enormous progress in other scientific fields such as exploration of marvels in our planet (structure and function of the earth and deep sea, or the protecting atmospheric layers covering our planet, and the enormous variety of life forms); or, the great advances in medicine and prolongation of life expectancy; or, the new findings about deep space and the universe, and the amazing aspirations of reaching to the stars.